Design and development of a brake system using smart materials - Johar, Muhammad Akmal (2007)
The research is done to fulfil the requirements of the Master of Mechatronic program at the University of Applied Sciences Ravensburg-Weingarten. This research is about designing a new concept of a brake system using smart materials. Smart materials are materials that receive, transmit or process a stimulus and respond by producing a useful effect. Smart materials have attracted researchers' attention in venturing a new technology that can improve our lives. There are a lot of materials that have been considered as smart materials. In this research a new type of material which is Ferromagnetic Shape Memory Alloy (FSMA) has been chosen. This alloy have significant advantages in term of producing a large scale of output effect and delivering fast response times compared to the other types of materials Based on these factors FSMA can be an appropriate material as an actuator for brake mechanism systems. After the invention of FSMA in early 1990s by Dr. Kari Ul\ako, lots of research laboratories has set up new research groups in order to have a better understanding about this material. Up to now they are still venturing the ways to develop this material as actuators. There are a lot of potential field of application such as couplers element, vibrators element, sensor and generator element, fluidic element and positioning devices. FSMA products that have been made available in the market are linear motor and fluidic pump from Adaptamat Ltd. FSMA has a big potential to replace current mechanical actuator and machinery such as pneumatic and hydraulic. In designing a brake system for robot applications there are several design constraints that need special attention. The design must be light and compact so that it will not become a significant additional load to the robot. In this robot application the brake system has a slightly different requirement. The brake torque is required to provide grips to the rotary shaft and not to stop the wheels. So in this application an initial braking torque is preferred. The research also gives special attention in finding an innovative way to improve the methodology of designing and developing mechatronic products. A new approach using the UML 2.0 has been used as a modelling technique. The technique is a well proven technique in the software engineering applications and with a minimum modification it is now suitable for the mechatronic engineering. Based on the results that have been achieved in this research the integration of the UML 2.0 with the Pahl and Beitz design methodology and the V-model has been successful.